Artificial intelligence databases: turn-on big data of the SMBs. (12th January 2022) - Manivannan, P.; Prabha, D.; Balasubramanian, K.
The small and medium businesses are working hard to make sense on the information data that has been collected from network sources and to translate it into tangible results. In fact, the major data growth trends and shifts in information. Big data have coined to generate and extremely more complex to associate in business databases. Most researcher work focuses on the relational database that requires lots of data processing. That's the reason, artificial intelligence (AI) can achieve input and ability to extend NoSQL document database depending on data type. This research recognises documented MongoDB as real-time access to data stored on various storage platform for all sizes of business. This paper proposed NoSQL-MongoDB model with data shared process embedded with AI and machine learning at the system-level by virtue datasets from the big data analytics. This methodology contributes a narrow view of database management turns on big data challenges for SMBs.